Errors in the Use of Indonesian Language Register by Foreign Learners in BIPA Learning - M. Wisnu Pawoko; Prima Vidya Asteria (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The appropriate use of language register is crucial in BIPA (Indonesian for Foreign Speakers) learning. However, many learners still struggle to adjust their language choice according to the communication context. This study aims to (1) describe the types of errors made by BIPA learners in choosing language register and (2) describe the factors causing these errors. Using a qualitative approach with the Systematic Literature Review (SLR) method, the study analyzed eight academic sources from the last 15 years, obtained from Google Scholar and Science Direct, focusing on errors in language register selection and BIPA learning. The findings reveal common errors, including difficulties distinguishing formal and informal registers, limited understanding of informal expressions, interference from native languages, confusion in recognizing language register differences, speaking anxiety, inappropriate use of formal registers in informal settings, impolite word choices, and use of informal registers in formal contexts. Contributing factors include limited awareness of audience-based register selection, insufficient practical learning, restricted vocabulary leading to interference, the influence of local dialects, nervousness and fear of mistakes, weak grammar knowledge, inappropriate word choices, and differing cross-cultural standards of politeness. These findings highlight the need for more contextual teaching materials in BIPA to enhance learners’ communicative competence.